Functioning stability of the railway passenger transportation system as aim of creation logical one - Hodoskina, O. A. (Science and Transport Progress, 2011)
The author considers the modern aspects of the railway transportation system in the Republic of Belarus. A description of a new innovative approach to the organization of passenger rail services is given. A comparative analysis of several important indices of rail freight and passenger traffic for the period 2005–2009 is presented. The need and possibility of constructing a logistics system for railway passenger transport are characterized.